Assessment of the Spatial Heterogeneity of Breast Cancers: Associations Between Computed Tomography and Immunohistochemistry. Issue 11 (May 2019) - Woolf, David K; Li, Sonia P; Detre, Simone; Liu, Alison; Gogbashian, Andrew; Simcock, Ian C; Stirling, James; Kosmin, Michael; Cook, Gary J; Siddique, Muhammad; Dowsett, Mitch; Makris, Andreas; et al.
Background: Tumour heterogeneity is considered an important mechanism of treatment failure. Imaging-based assessment of tumour heterogeneity is showing promise but the relationship between these mathematically derived measures and accepted 'gold standards' of tumour biology such as immunohistochemical measures is not established. Methods: A total of 20 women with primary breast cancer underwent a research dynamic contrast-enhanced computed tomography prior to treatment with data being available for 15 of these. Texture analysis was performed of the primary tumours to extract 13 locoregional and global parameters. Immunohistochemical analysis associations were assessed by the Spearman rank correlation. Results: Hypoxia-inducible factor-1α was correlated with first-order kurtosis ( r = −0.533, P = .041) and higher order neighbourhood grey-tone difference matrix coarseness ( r = 0.54, P = .038). Vascular maturity-related smooth muscle actin was correlated with higher order grey-level run-length long-run emphasis ( r = −0.52, P = .047), fractal dimension ( r = 0.613, P = .015), and lacunarity ( r = −0.634, P = .011). Micro-vessel density, reflecting angiogenesis, was also associated with lacunarity ( r = 0.547, P = .035). Conclusions: The associations suggest a biological basis for these image-based heterogeneity features and support the use of imaging, already part of standard care, for assessing intratumoural heterogeneity.